Potentially inappropriate medications (PIMs) in older hospital in‐patients: Prevalence, contribution to hospital admission and documentation of rationale for continuation. (11th March 2016) - Ní Chróinín, Danielle; Neto, Hugo M; Xiao, Diane; Sandhu, Anmol; Brazel, Carly; Farnham, Nell; Perram, Jacinta; Roach, Timothy S; Sutherland, Emily; Day, Ric; Beveridge, Alexander
Abstract : Aim: To establish prevalence, sequelae and documentation of potentially inappropriate medication (PIM) use in older hospital in‐patients. Methods: Notes of all patients ≥65 years old, admitted to our tertiary teaching hospital (January 2013), were retrospectively reviewed, and the Screening Tool of Older Persons' potentially inappropriate Prescriptions applied. Results: Amongst 534 patients, 54.8% (284) were on ≥1 PIM at admission, 26.8% on multiple; 60.8% were discharged on a PIM. Six percent of all admissions were potentially attributable to a PIM; falls associated with risk therapies were commonest (23/30), and often (65.2%) associated with serious injury. Pre‐specified subgroup analysis ( n = 100) identified 101 PIMs‐at‐discharge amongst 47 patients. In 82.2%, a clinical rationale for continued prescription was documented, with this communicated to the GP by letter in 71.1%. Conclusion: PIMs were common, and contributed to admission and injury. Hospitalisation provides an opportunity for medication rationalisation, and documentation of rationale for any PIM use.